Spanish National Hip Fracture Registry (RNFC): analysis of its first annual report and international comparison with other established registries - Ojeda-Thies, C; Sáez-López, P; Currie, CT; Tarazona-Santalbina, FJ; Alarcón, T; Muñoz-Pascual, A; Pareja, T; Gómez-Campelo, P; Montero-Fernández, N; Mora-Fernández, J; Larrainzar-Garijo, R; Gil-Garay, E; et al. (Springer, 2019)
Summary Hip fracture registries have helped improve quality of care and reduce variability, and several audits exist worldwide. The results of the Spanish National Hip Fracture Registry are presented and compared with 13 other national registries, highlighting similarities and differences to define areas of improvement, particularly surgical delay and early mobilization.